2009
DOI: 10.1002/er.1560
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of granular phase changing composites for thermal energy storage using the T-history method

Abstract: SUMMARYThe present article reports on the characterization of granular phase changing composites using the T-history method. Further modifications and improvements of the method are employed to handle granular materials undergoing phase change over a temperature range. The accuracy of the T-history method is shown to be limited by the assumption of temperature-independent specific heats and the difficulty of determining the limits of solid and liquid phases. The concept of enthalpy and its relationship with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Details on the experimental set-up and data analysis for GR27 and GR41 can be found in [9]. Characterizing granulate PCMs using DSC requires special care to assure that the thermophysical properties of samples (1-10 mg) are those of the bulk materials.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the experimental set-up and data analysis for GR27 and GR41 can be found in [9]. Characterizing granulate PCMs using DSC requires special care to assure that the thermophysical properties of samples (1-10 mg) are those of the bulk materials.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Direct utilization of the measured DSC curves could result in an inexact representation of the sample enthalpy change. A simple procedure has been advised to obtain accurate results from the DSC measurements based on the estimation of the thermal resistance between the sample and its enclosure [9]. The thermal resistance between the GPCC sample and it container is evaluated using DSC measurements obtained at three different values of cooling/heating rates.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Both heating and cooling curves are presented for each method. In addition, Rady et al (2010) evaluated the T-history method for characterization of granular PCM composites. Furthermore, Li et al (2012) reported that the maximum discrepancies between T-history measurements of eutectic salt mixtures and the results of DSC testing were less than 8 %.…”
Section: T-history Methodsmentioning
confidence: 99%
“…Also, methods to determine stratification efficiency of TES processes have been reviewed and compared (Haller et al 2009). Performance of thermal storage utilizing microcapsule phase change materials (Fang et al 2010) and granular phase change composites (Rady et al 2010) has also been examined, as have isothermal storage methods of solar energy for buildings (Heim 2010). Long-term test results have been reported from a latent heat storage for solar heating and cooling (Himpel et al 2010).…”
Section: Performancementioning
confidence: 99%